Urgensi Mindset Tumbuh (Growth Mindset) Dalam Meningkatkan Motivasi Belajar Peserta Didik - Nasril Nasar Nasril (SALIHA: Jurnal Pendidikan & Agama Islam, 2023)
The urgency of the growth mindset on students' learning motivation is something that needs to be studied, because motivation is influenced by mindset. This study aims to determine the extent to which the urgency of the growth mindset affects students' learning motivation. This study used a qualitative research method with a library research approach (literary study). Literature studies in this paper are written works that have been published, in this case in the form of books and articles that have been published in a journal. To draw conclusions or results, this literature study goes through several stages, namely: ensuring the sources reviewed are in line with the research title. Furthermore, the contents in the literature are adjusted to the research title. Then finally, the contents of the source in accordance with the research title, a summary is made so as to produce a new idea. The results of this study indicate that the growth mindset possessed by each student has the power to bring out student behavior. The strength of the growth mindset possessed by students will make students have positive learning concepts and behaviors. In the sense that students go through the learning process with the belief that intelligence can be developed through serious learning and experiences